PENTINGNYA PENDIDIKAN MULTIKULTURAL - Puspita, Yenny (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract--- Multicultural education is an education based on the principles and principles of multiculturalism that is the concept of diversity that recognizes, accepts and affirms human differences and equations associated with gender, race and class, religion based on values and democratic understanding that builds cultural pluralism in the fight against prejudice and discrimination. As for the importance of multicultural education in Indonesia that is as an alternative means of conflict resolution, learners are expected to leave no cultural roots, and highly relevant multicultural education is used for existing democracy as it is now Keywords: Education, Multicultural  Abstrak— Pendidikan multikultural adalah pendidikan yang berlandaskan pada asas dan prinsip konsep multikulturalisme yakni konsep keberagaman yang mengakui,menerima dan menegaskan perbedaan dan persamaan manusia yang dikaitkan dengan gender, ras, dan kelas,agama berdasarkan nilai dan paham demokratis yang membangun pluralisme budaya dalam usaha memerangi prasangka dan diskriminasi. Adapun pentingnya pendidikan multikultural di Indonesia yaitu sebagai sarana alternatif pemecahan konflik, peserta didik diharapkan tidak meninggalkan akar budayanya, dan pendidikan multikultural sangat relevan digunakan untuk demokrasi yang ada seperti sekarang. Kata Kunci— pendidikan,  multikultural